Endoparasites of household and shelter cats in the city of Rio de Janeiro, Brazil - Ramos,Nilcéia de Veiga (2020)
Abstract Endoparasitic infections are associated with morbidity in cats. This study aimed to investigate the occurrence of endoparasites among cats of different life stages in the city of Rio de Janeiro, Brazil. The samples were analyzed individually by macroscopic exploration for proglottids and centrifugal-flotation. Stool samples were obtained from household cats (n = 57) and shelter cats (n = 336). Endoparasites were detected in 50.64% of the samples. Among household and shelter cats, 21.05% and 55.66% were infected with endoparasites, respectively. In household cats, the most prevalent endoparasites were Ancylostoma spp. (in 25.0%) and Strongyloides spp. (in 25.0%), followed by Toxocara spp. (in 16.67%), Dipylidium caninum (in 16.67%), Cystoisospora spp. (in 8.33%), and Uncinaria spp. + Ancylostoma spp. (in 8.33%). In shelter cats, the most prevalent endoparasite was Ancylostoma spp. (in 29.41%), followed by Cystoisospora spp. (in 26.20%) and Toxocara spp. (in 16.58%), as well as Cystoisospora spp. + Toxocara spp. (in 8.02%); Ancylostoma spp. + Toxocara spp. (in 11.76%); Cystoisospora spp. + Ancylostoma spp. (in 3.74%); Cystoisospora spp. + Toxocara spp. + Ancylostoma spp. (in 3.21%); and Dipylidium caninum + Ancylostoma spp. (in 0.53%). Endoparasitic infections in cats underscore the need for preventive veterinary care and routine coproparasitologic tests.